Effect of Garlic (Allium sativum) and Turmeric (Curcuma domestica Val.) Extract Combination in Type 2 Diabetic Rats. - Ndruru, Titi Marlina; Simanjuntak, Nerly Juli Pranita; Novriani, Erida (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
Type 2 diabetes mellitus (T2DM) often leads to kidney damage due to chronic hyperglycemia and oxidative stress. Garlic (Allium sativum) and turmeric (Curcuma domestica Val.) are traditional medicinal plants with known antioxidant and anti-inflammatory properties. This study evaluated the nephroprotective effect of their combined extracts in streptozotocin (STZ)-induced diabetic rats. Twenty-five male rats were divided into five groups: negative control, positive control (metformin 500 mg/kg BW), and three treatment groups receiving extract combinations at doses of 100, 200, and 300 mg/kg BW. Blood glucose, urea, and creatinine levels were measured, followed by histopathological examination. Phytochemical analysis confirmed the presence of alkaloids, flavonoids, and other secondary metabolites. Although statistical analysis showed no significant difference in glucose, urea, and creatinine levels among groups (p > 0.05), the 200 mg/kg BW group exhibited the most favorable trends in reduced blood glucose (226.70 ± 89.70 mg/dL) and kidney biomarkers. These results suggest the combination extract may offer protective effects on kidney function in diabetic conditions, warranting further investigation.